Electronic payment systems in electronic commerce - Atabay Kuşçu, Rana; Çiçekcisoy, Yasemin; Bozoklu, Ümit (IGI Global, 2019)
Technological advances and correspondingly the spreading usage of the Internet have significantly changed commerce, and also the concept of money has become more abstract. Customers with the help of the technological advances don't have the necessity of cash money, and consumers/firms tend towards alternative payment methods. At this point, electronic commerce (e-commerce) web sites have started to use block chaining payment methods. In this digital world, new payment technologies have started to spread far and wide thanks to fast improvements in payment technologies, and they offer different options in payment methods. Each electronic payment (e-payment) system has some advantages; however, each of them has some disadvantages as well. The aim of this study is to investigate the e-payment systems which are different from traditional payment methods.
Keywords: Electronic Payment Systems; Electronic Commerce; Technological Advances